Restitution as a Form of Protection against the Rights of the Child Victims - Eko Febrianto (UNISSULA Semarang, 2021)
This study aims to determine and analyze how the mechanism for implementing restitution for child victims of crime. This research uses normative juridical writing method. The results of this study are that in the Government Regulation of the Republic of Indonesia Number 43 of 2017 concerning the Implementation of Restitution for Children Who Become Victims of Crime, it still has shortcomings, especially regarding substitute punishment if the decision to grant restitution is not implemented, it is not regulated in this government regulation, so hope that This government regulation will serve as a legal umbrella for children who are victims of criminal acts by adding in these government regulations additional penalties, in addition to corporal punishment and fines as the main crime, so that legal certainty for the implementation of restitution for children who become victims of these crimes can be implemented. .